The Effect of Short Education Movies (SEM) on the Level of Knowledge of Adolescents in Preventing Bullying - Widya Kinanti Putri; Arifal Aris; Abdul Majid (Jurnal Ilmiah Kesehatan)
Bullying is a negative behaviour that uses power to hurt individuals or groups verbally, physically or psychologically until the victim feels traumatised, pressured and helpless. This can occur due to a lack of knowledge among teenagers regarding bullying behaviour. This research aims to determine the effect of Short Education Movies (SEM) on the level of knowledge of teenagers in preventing bullying. This research uses pre-experimental techniques with a one-group pre-test/post-test design approach. The research sample was 36 teenagers taken based on inclusion and exclusion criteria using a sampling technique, namely purposive sampling. The results of the analysis obtained through the Wilcoxon signed-rank test on the pre-test and post-test on the knowledge variable are p=0.000 with a significance standard of p<0.05, which means there is an influence of the Short Education Movie (SEM) on the level of knowledge of teenagers in preventing bullying. Based on the results of this research, it is hoped that health workers, especially community nurses, can use short films as a health education medium to increase knowledge about bullying in teenagers.